Diversity and abundance of macroalgal assemblages along the eastern coastline of Northern Samar, Philippines - Mejica, Lynne Adrienne O. (2017)
Macroalgal species play a vital role in marine biodiversity. In the Philippines, several species of seaweeds can be found. Thus, local and foreign phycologists have been conducting macroalgal studies all throughout the country. However, the towns along the eastern coastline of Northern Samar remain understudied. This study was conducted to identify the different species of macroalgae and characterize the species diversity patterns in the towns of San Policarpo, Arteche, Lapinig, Gamay and Mapanas in the eastern coastline of Northern Samar. Using the random quadrat sampling method, the areas were assessed from January to February 2017. A total of 62 species were identified including 22 species of Chlorophyta, 15 species of Phaeophyta, and 25 species of Rhodophyta. San Policarpo had the highest mean percent cover of (93.47% cover per meter square plus or minus 3.87) seaweed species. It was followed by Lapinig (88.85% cover per meter square plus or minus 3.1), Gamay (81.87% cover per meter square plus or minus 1.53), Arteche (74.13% cover per meter square plus or minus 2.35) and Mapanas (62.93% cover per meter square plus or minus 1.66). Gamay had the highest diversity with 33 species, Lapinig had 18 species, Mapanas had 17 species, Arteche had 15 species and San Policarpo had the lowest diversity with 14 species. Among the species identified, Sargassum polycystum was the most abundant in all of the sites. Moreover, 41 macroalgal species were identified which were not previously reported by Silva et al. in 1987. This study serves as a new baseline record for future biomonitoring studies and further investigation of the potentials of locally available seaweeds. Advanced systematic studies on these seaweed resources may provide useful data for the conservation of marine algal resources in these sites.